2016
DOI: 10.22495/cocv13i2c2p7
|View full text |Cite
|
Sign up to set email alerts
|

The ownership structure effect on firm performance in South Africa

Abstract: This research investigates the effect of corporate governance through ownership structures; ownership concentration, managerial ownership and government ownership on firm performance. A multiple regression analysis was employed on sample data collected over ten years from 2001-2010 from 80 South African companies to test the magnitude of their influence to company performance as measured by return on assets (ROA). This study found a positive and significant correlation between ownership concentration, governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
1
14
1
Order By: Relevance
“…Consistent with previous studies of Cameron (2012), Mugobo et al (2016) in South Africa, this study found that the coefficient of the ownership concentration is negative and statistically significantly related to firm value measures of Tobin's Q and ROA. This finding is contrary to Berle and Means (1932), who proposed the importance of large shareholders to reduce corporate risk and increase corporate performance.…”
Section: Ownership Concentration and Firm Valuesupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies of Cameron (2012), Mugobo et al (2016) in South Africa, this study found that the coefficient of the ownership concentration is negative and statistically significantly related to firm value measures of Tobin's Q and ROA. This finding is contrary to Berle and Means (1932), who proposed the importance of large shareholders to reduce corporate risk and increase corporate performance.…”
Section: Ownership Concentration and Firm Valuesupporting
confidence: 91%
“…ROA, the accounting base of measuring firm value, is 10.04 on average with a minimum and maximum value of -845 to 105, respectively, during the study period from 2004 to 2016. It is lower than that observed by Mugobo et al (2016) with 16.0 and Zondi and Sibanda (2015) with 14.73. The average value of ownership concentration (OC) measured by the number of percentage share with a vote held by large five shareholders on the JSE equity market is 40.10%, and this is higher than the 32.36% reported by Steyn and Stainbank (2013) on the same stock exchange in South Africa.…”
Section: Empirical Findings 61 Descriptive Statisticscontrasting
confidence: 60%
See 1 more Smart Citation
“…The ownership structure is seen as one of the most important mechanisms of corporate governance, and it becomes particularly important in conditions characterized by a high degree of ownership concentration (ÁVILA;ROCHA;DA SILVA, 2015;CONNELLY, et al, 2010;DEMSETZ;VILLALONGA, 2001;FACCIO;FILATOTCHEV, et al, 2007;HOLDERNESS, 2017;ILHAN-NAS, et al, 2018;KALEZIĆ, 2015;SHLEIFER, 1999;LEPORE, et al, 2017;MUGOBO;MUTIZE;ASPELING, 2016;VISHNY, 1986;SINGLA;GEORGE;VELIYATH, 2017;STULZ, 2005;SURESHA;RAVIKUMAR, 2018;THOMSEN;PEDERSEN, 2000;VEGA SALAS;DENG, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we witnessed a surge in research from all over the world that are increasingly investigating the impact of ownership structure on the performance of corporations (ÁVILA, et al, 2015;ILHAN-NAS, et al, 2018;KALEZIĆ, 2015;MUGOBO, et al, 2016). A number of those researchers have identified that in many jurisdictions around the world ownership is concentrated (sometimes highly concentrated) in the hands of few -one or more large shareholders (BARCA; BECHT, 2002;LA PORTA, et al, 1999;MAURY;PAJUSTE, 2005).…”
Section: Introductionmentioning
confidence: 99%